Answer:
12a^2 - 9a + 5
Step-by-step explanation:
(5a^2 - 6a - 4) - (-7a^2 + 3a - 9)
5a^2 + 7a^2 = 12a^2
-6a - 3a = -9a
-4 + 9 = 5
12a^2 - 9a + 5
Answer:
independent
Step-by-step explanation:
We put the independent variable on the x axis ( or horizontal) and the dependent variable on the y axis ( or vertical)
Luckly i still have my notes and the answer was about 3.1%. I hope this helped.
Answer:
Step-by-step explanation:
question 6
1 to 11.5
line 1
3 to 34.5
line 2
5 to 57.5
line 3
8 to 92
line 4
8.5 to 97.75
line 5
11 to 126.5
line 6
12 to 138
hope that helped
Answer:
see below
Step-by-step explanation:
Use the distributive property:
(y^2 +3y +7)(8y^2 +y +1)
= y^2(8y^2 +y +1) +3y(8y^2 +y +1) +7(8y^2 +y +1)
= 8y^4 +y^3 +y^2 + 24y^3 +3y^2 +3y + 56y^2 +7y +7
= 8y^4 +y^3(1 +24) +y^2(1 +3 +56) +y(3 +7) +7
= 8y^4 +25y^3 +60y^2 +10y +7 . . . . . matches the last choice